Isu Utama dalam Non-Fungible Token (NFT): Bagaimana Pengalihan Hak Cipta Harus Beradaptasi? - Alif Muhammad Gultom; Fitri Astari Asril (Perspektif Hukum, 2023)
Non-fungible tokens, also known as NFTs, are a special kind of digital record of ownership that is utilized in a certain manner to guarantee validity and uniqueness of intangible goods. Due to its features, NFTs become interesting among art creators and even asset collector. Transactions on NFT create incredible values, which raises a number of legal issues, particularly in the realm of intellectual property rights related to copyright. This research aims to explains the connection between the existence of NFT and current copyright law in Indonesia focusing on the ownership and transfer of rights from the purchasing of NFTs. The author will try to compare on other jurisdictions (Ireland & Germany) concerning the copyright legal framework. Furthermore, the practice by licensing method in current NFTs marketplace will also be demonstrate through this paper. The research methodology employed is a normative juridical approach with an analytical and descriptive research design. Based on the research conducted, there is still a legal gap in Indonesian copyright law, particularly in the realm of NFTs and the idea of droit de suite, which has existed in intellectual property right concept globally. Finally, this paper will present several recommendations for the government and other relevant stakeholders upon NFTs transactions.